2014
DOI: 10.1002/pon.3708
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Documentation for Psycho-Oncology Short Form (PO-Bado SF)-an expert rating scale for distress screening: development and psychometric properties

Abstract: The PO-Bado SF is a short, reliable and valid expert rating scale to identify distressed cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Researchers found prevalence rates between 23% and 60% . Herschbach et al (2004) reported 36%, Zabora et al (2001) 35%, Mitchell et al (2011) 39%, and Mehnert et al (2018) 52% . The range of the sample sizes of these studies is between n = 303 9 and n = 6414 …”
Section: Introductionmentioning
confidence: 94%
“…Researchers found prevalence rates between 23% and 60% . Herschbach et al (2004) reported 36%, Zabora et al (2001) 35%, Mitchell et al (2011) 39%, and Mehnert et al (2018) 52% . The range of the sample sizes of these studies is between n = 303 9 and n = 6414 …”
Section: Introductionmentioning
confidence: 94%
“…One explanation for these lower numbers could be that a specific definition of 'psychosocial distress' has not been determined, which is why distress is often assessed within the scope of psychiatric disorders (e.g. anxiety disorders) or reduction in quality of life (23). The prevalence of distress is therefore somewhat incomparable between different studies unless the same definitions are applied.…”
Section: Discussionmentioning
confidence: 99%
“…All enrolled participants were screened for psychosocial distress using the Basic Documentation for Psycho-Oncology Short Form (PO-Bado SF) (23) at three defined time points (T1-T3): T1 (basic hospital assessment): within the course of inpatient admission to the orthopedic ward prior to surgery; T2 (repeat hospital assessment): after surgery on the day before discharge from the surgical ward; T3 (follow-up assessment): during clinic review, 3 months after the operation. PO-Bado screening was performed at all time points by orthopedic doctors who were trained in conducting the standardized interview according to the published guidelines prior to the start of this study (23). Patients who exceeded the defined cut-off value of more than 9 points in the PO-Bado SF were assumed to be highly psycho-oncologically distressed and were offered psychosocial support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total score of 8 or greater on the PO-Bado SF is recommended to recognize patients with clinically relevant distress [ 17 ], however it has not been validated in brain tumor patients so far. Marten-Mittag et al conducted an analysis comparing – inter alia - the Distress Thermometer (DT) values of 1551 cancer patients (clinically relevant distress: DT > 4) and the results of PO-Bado SF results scored by physicians and found a total score of 9 or greater to be optimal [ 18 ]. However, in the patient sample there were rare brain tumor patients.…”
Section: Introductionmentioning
confidence: 99%